The Effect of Infant Formulas With 4 or 8 g/L GOS/FOS on Growth, Gastrointestinal Symptoms, and Behavioral Patterns: A Prospective Cohort Study - Karina Merini Tonon PhD; Thaís Moreno Tomé BSND; Elaine Martins Bento Mosquera; Natália Pratis Perina PhD; Tamara Lazarini MSc (SAGE Publishing, 2021)
There is a lack of studies investigating the clinical benefits of prebiotic-supplemented infant formula. In this study, healthy infants that started, on medical recommendation, artificial feeding with one of 2 infant formulas containing 4 g/L of GOS/FOS (9:1) (IF4 group; n = 60) or 8 g/L of GOS/FOS (9:1) (IF8 group; n = 60) were followed for 30 days to the evaluation of growth and gastrointestinal symptoms. Exclusively breastfed infants (EBF; n = 60) were followed up as a reference. Both infant formulas supported adequate weight gain, however, IF4 formula promotes growth more similar to breastfed infants. There was no additional benefit of a dose higher than 4 g/L of GOS/FOS on gastrointestinal symptoms.